Analysis of the Variability in the Atmospheric Electric Field and Natural Gamma Radiation in Different Weather Conditions - Rosa de Oliveira, Rafael Ricardo (2021)
In recent years the analysis of the variability of the natural gamma radiation and its relationshipwith high atmospheric electric fields in disturbed weather, e.g., thunderstorms, have been important, as well as the relationship between these parameters in fair weather conditions. In this paper we analyze the diurnal variation of the atmospheric electric field and natural gamma radiation, in fair and disturbed weather conditions, recorded in the Argentinian Andes mountain (2552 masl) between April 2018 and February 2019. In fair weather conditions, it was found a higher linear correlation coefficient (R) between the atmospheric electric field diurnal curve and the ‘universal’ Carnegie curve (R=0.93), and a high negative correlation between the atmospheric electric field and natural gamma radiation diurnal curve (R=-0.9). On the other hand, in disturbed weather conditions, we reported thirteen events where it was found intense natural gamma radiation enhancements associated with high atmospheric electric field variability. A maximum of 35 % excess in the natural gamma radiation was detected, which was associated with thunderstorms and rain precipitation. It was observed a high correlation between the excesses of the gamma natural radiation enhancement with the atmospheric electric field values (R=0.80) and with the rain precipitation rate (R=0.59).